2018
DOI: 10.1111/acv.12450
|View full text |Cite
|
Sign up to set email alerts
|

Lower levels of glucocorticoids in crop‐raiders: diet quality as a potential ‘pacifier’ against stress in free‐ranging Asian elephants in a human‐production habitat

Abstract: Overlapping habitats and sharing of resources between elephants and people has led to intense elephant-human conflicts, especially crop depredation by elephants, across elephant-range countries. While raiding agricultural crops, elephants face numerous threats from people through chase, injury and the risk of death which could enhance the associated energetic costs, ultimately elevating their stress levels. We hypothesized that crop-raiders (in the human-production habitat) would show higher faecal glucocortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…For instance (Stabach et al, 2015) observed an inverse relationship between FGM concentrations and NDVI in wildebeest in Kenya. Pokharel et al (2019) also confirmed an inverse proportionality between FGM concentrations and NDVI in free-ranging Asian elephants in India, while Hunninck et al (2020) found an inverse relationship between FGM concentrations and NDVI in impalas in the Serengeti ecosystem. Our study was limited by having fewer samples collected during the dry season (end of April to mid-May); nevertheless, our findings confirm the influence that vegetation quality potentially has on the adrenal response of wildlife.…”
Section: Influence Of Ndvi On Fgmmentioning
confidence: 58%
See 1 more Smart Citation
“…For instance (Stabach et al, 2015) observed an inverse relationship between FGM concentrations and NDVI in wildebeest in Kenya. Pokharel et al (2019) also confirmed an inverse proportionality between FGM concentrations and NDVI in free-ranging Asian elephants in India, while Hunninck et al (2020) found an inverse relationship between FGM concentrations and NDVI in impalas in the Serengeti ecosystem. Our study was limited by having fewer samples collected during the dry season (end of April to mid-May); nevertheless, our findings confirm the influence that vegetation quality potentially has on the adrenal response of wildlife.…”
Section: Influence Of Ndvi On Fgmmentioning
confidence: 58%
“…Differences in FGM concentrations of elephants at Mpala Ranch could be attributed to non-residents having access to higher quality diets due to greater foraging, resulting in lower FGM concentrations. In India Pokharel et al (2019) also observed lower FGM concentrations among crop raiding elephants, which was speculated to act as a mitigator against stress compared to elephants in protected forests with limited calorie-dense food sources.…”
Section: Influence Of Ranging Behavior On Fgmmentioning
confidence: 93%
“…For instance, (Stabach et al, 2015) observed an inverse relationship between FGM concentrations and NDVI in wildebeest in Kenya. Pokharel et al (2019) also confirmed an inverse proportionality between FGM concentrations and NDVI in free-ranging Asian elephants in India, while Hunninck et al (2020) found an inverse relationship between FGM concentrations and NDVI in impalas in the Serengeti ecosystem. Our study was limited by having fewer samples collected during the dry season (end of April to mid-May);…”
Section: Influence Of Ndvi On Fgmmentioning
confidence: 58%
“…Although elephant home ranges are restricted to both artificial and permanent water sources during the dry season (Chamaillé-Jammes et al, 2013;Purdon & Van Aarde, 2017), they are known to track peak forage quality (Loarie et al, 2009) to improve their energy balance which could have resulted in lower FGM concentrations in non-resident elephants at Mpala Ranch. Although the physiological demands of ranging over long distances exposes animals to stressful environments (Wilcove & Wikelski, 2008), access to better forage quality could act as a potential 'pacifier' against stress (Pokharel et al, 2019) which then leads to lower FGM concentrations among non-resident elephants. Shaw & Couzin (2013) Manuscript to be reviewed known to switch diets depending on seasonality (Kartzinel et al, 2019) and land use.…”
Section: Influence Of Ranging Behavior On Fgmmentioning
confidence: 99%
“…However, while NDVI has been found to be a good surrogate of total vegetation biomass/primary productivity in various habitats (examples: savannahs: Sjöström et al., ; Wu, De Pauw & Helldén, ; savannah–steppe mixed landscapes: Sannier, Taylor & du Plessis, ; shrublands: Wilson, Silander, Gelfand & Glenn, ; tropical forests: Roy & Ravan, ; Madugundu, Nizalapur & Jha, ; Das & Singh, ), tests of whether NDVI or other similar indices actually reflect the abundance or quality of vegetation relevant to the focal animal are unfortunately rare and largely restricted to open habitats such as grasslands and savannahs (e.g., Kawamura et al., ; Ryan et al., ; Zengeya, Mutanga & Murwira, ). We could find only one such study in temperate forest (Borowik, Pettorelli, Sönnichsen & Jędrzejewska, ) and one from a tropical forest habitat (Willems et al., ), despite the use of NDVI in studies of animal ecology in those habitats (Lakshminarayanan, Karanth, Goswami, Vaidyanathan & Karanth, ; Marasinghe, Dayawansa & de Silva, ; Pokharel, Singh, Seshagiri & Sukumar, ; Rahman et al., ; Rood et al., ; Srinivasaiah, Anand, Vaidyanathan & Sinha, ; Zinner et al., ). If remotely sensed indices do not reflect forage abundance, their use in studies of foraging and habitat use would lead to artifactual results.…”
Section: Introductionmentioning
confidence: 99%